2019
DOI: 10.1200/jco.2019.37.15_suppl.3542
|View full text |Cite
|
Sign up to set email alerts
|

cfDNA for accurate determination of RAS and BRAF mutations using OncoBEAM liquid biopsy in metastatic colorectal cancer patients: Results of the real-world multicentric ColoBEAM study.

Abstract: 3542 Background: Determination of KRAS, NRAS ( RAS) and BRAF mutations is a standard of care for the management of patients with metastatic colorectal cancer (mCRC). RAS mutations are well characterized resistance biomarkers to anti-EGFR antibodies and BRAF V600 mutations indicate poor prognosis. Tissue biopsy has traditionally been used to determine RAS and BRAF status, but liquid biopsy analysis of circulating tumor DNA (ctDNA) has demonstrated utility as a less invasive tool to expedite molecular testing r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…In a prospective-multicenter study, Thierry and colleagues show that cfDNA analysis could advantageously replace tumor-section analysis for KRAS and BRAF mutations [168]. These findings are in line with results from the ColoBEAM study, where BEAMing assay technology confirmed high overall tissue and blood concordance for RAS/BRAF of 89.3% (Se = 87.5%; Sp = 92.0%) in chemotherapy-naïve patients [171]. These studies highlight that cfDNA extracted from plasma is an attractive surrogate marker to tissue DNA biopsy for KRAS, NRAS and BRAF mutation assessment ( Table 2).…”
Section: Circulating Tumor Dna (Ctdna) and Cell-free Dna (Cfdna)mentioning
confidence: 66%
See 1 more Smart Citation
“…In a prospective-multicenter study, Thierry and colleagues show that cfDNA analysis could advantageously replace tumor-section analysis for KRAS and BRAF mutations [168]. These findings are in line with results from the ColoBEAM study, where BEAMing assay technology confirmed high overall tissue and blood concordance for RAS/BRAF of 89.3% (Se = 87.5%; Sp = 92.0%) in chemotherapy-naïve patients [171]. These studies highlight that cfDNA extracted from plasma is an attractive surrogate marker to tissue DNA biopsy for KRAS, NRAS and BRAF mutation assessment ( Table 2).…”
Section: Circulating Tumor Dna (Ctdna) and Cell-free Dna (Cfdna)mentioning
confidence: 66%
“…There are a large number of studies that have correlated cfDNA with BRAF and KRAS tissue mutations [168,[171][172][173]. In a prospective-multicenter study, Thierry and colleagues show that cfDNA analysis could advantageously replace tumor-section analysis for KRAS and BRAF mutations [168].…”
Section: Circulating Tumor Dna (Ctdna) and Cell-free Dna (Cfdna)mentioning
confidence: 99%
“…Various commercial platforms are available for identifying actionable mutations in CRC such as Idylla or OncoBEAM, Idylla platform being used also for MSI detection (201)(202)(203). Vidal and colleagues (204) revealed a 93% overall agreement between the mutational status of RAS when comparing tissue and plasma samples.…”
Section: Circulating Tumor Nucleic Acids (Ctnas)mentioning
confidence: 99%
“…Taking anti-EGFR therapy as an example [ 125 127 , 131 ], ctDNA studies demonstrate that RAS/EGFR mutant clones emerge during treatment, which might regress upon the withdrawal of anti-EGFR therapy, thereby allowing for rechallenge with the targeted therapy [ 128 ]. This regression could not be reasonably assessed using tumor tissue because it would mean the risk of repeated biopsying.…”
Section: Molecular Profiling In the Bloodmentioning
confidence: 99%